Urgensi Layanan Konseling pada Pernikahan Beda Agama - Musyrifin, Zaen (Madaniyah, 2018)
This article describes the importance of counseling services to married couples with different religions. Counseling services need to be done because there are still pros and cons related to different religious marriages. Counseling services need to be done to help consolidate the heart for potential couples of different religions who will decide to marry and for married couples. This is because marriage partners of different religions must have problems, either before deciding to marry or after marriage and live married life. The focus of counseling services is the problem of interaction in living the household. Different religious marriage counselors may act as moderators, counselors or advisers, as well as saviors of marriage and family relationships. The method used in this research is by library study approach. This approach is applied to find concepts related to religious marriage counseling with the aim of increasing the treasury of guidance and counseling in the setting of society.Â Key Words: Counselling, Marriage Different Religion.